Lexical and semantic characteristics of hyponomic relations in English linguistics - JUMAEVA NASIBA KOMIL KIZI (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article describes the lexical and semantic relation of hyponims in English linguistics, which means that analyzing deeply the features of hyponims and its characteristic features. One of the most vital progresses in cognitive understanding of information, one of the extremely significant device to classifing voacabulary and performing of the human perception. Lexical and semantic relations of hyponims are taken into consideration important when giving logical meaning and connection to speech that help to express the meaning of the word.